P617 Molecular typing of mycoplasma genitalium shows a diverse epidemic with limited azithromycin resistance in south africa. (14th July 2019) - Laumen, Jolein; Alphen, Lieke Van; Maduna, Liteboho; Medina-Marino, Andrew; Mcintyre, James; Klausner, Jeffrey; Kock, Marleen; Peters, Remco
Abstract : Background: The occurrence of azithromycin resistance in M. genitalium infection is unknown in Africa, where diagnostic resources are limited and STIs are managed syndromically. This study aims to gain insight in the molecular epidemiology including antimicrobial resistance of M. genitalium infection in South Africa. Methods: We collected 87 M . genitalium- positive samples obtained from participants in three study cohorts: HIV-infected pregnant women residing in townships in Pretoria (n=44), men and women accessing primary healthcare services in rural Mopani District (n=32), and men accessing sexual health services in Johannesburg (n=11). Molecular typing was performed using single nucleotide polymorphism (SNP) analysis of the MG191 gene to determine sequence type (ST) combined with variable-number of tandem-repeat (VNTR) assessment of the MG309 gene. Molecular detection of macrolide resistance-associated mutations in the 23S rRNA gene was done and, if detected, subsequent sequencing of the parC and gyrA genes for quinolone resistance. Results: SNP analysis was successful in 22 specimens and showed 17 different STs (9 known and 8 new STs). VNTR assessment was successful for 36 specimens and showed variation in the number of repeat, ranging from 8 to 19; four strains had the same number of repeats (11). There was no geographic clustering of specific STs or number of repeats observed. Azithromycin resistance was detected in only 1/87 specimens (1.1%); a mutation in the parC gene associated with quinolone resistance was also detected in this case. This specific strain was a unique novel ST, but with similar tandem repeats, compared to the drug-susceptible stains. Conclusion: This study shows a well-established, genetically diverse epidemic of M. genitalium infection in South Africa. The prevalence of azithromycin resistance was low, which is probably the result of the relatively recent introduction of azithromycin in the syndromic management guidelines. Nevertheless, introduction of diagnostics and surveillance of resistance is urgently warranted. Disclosure: No significant relationships.